Clinical Impact of HAb18G/CD147 Expression in Esophageal Squamous Cell Carcinoma - Zhu, Shaojun; Li, Yanhong; Mi, Li; Zhang, Yang; Zhang, Li; Gong, Li; Han, Xiujuan; Yao, Li; Lan, Miao; Chen, Zhinan; Zhang, Wei (Digestive diseases and sciences, 2011)
Background HAb18G/CD147 expression has been associated with many tumor invasion molecules, which play important roles in recurrence and poor differentiation of esophageal squamous cell carcinoma (ESCC). However, the clinical implications of HAb18G/CD147 in ESCC are still unclear. Aims In this study, we clarified the clinical significance of HAb18G/CD147 and characterized the association between HAb18G/CD147 and tumor invasion in ESCC cases. Methods Tumor tissues were obtained from 86 ESCC patients who underwent surgical resection between 2002 and 2005. All patients that had received previous therapy were excluded. ESCC tissues were analyzed by IHC using anti HAb18G/CD147 antibody. The expression of HAb18G/CD147 mRNA in esophageal cancer cell lines was analyzed by RT–PCR. Results HAb18G/CD147 was uniformly expressed in EC109 and EC871214 cell lines, but negatively expressed in EPC2, esophageal normal squamous cell line. HAb18G/CD147 mainly localized to the membrane of tumor cells in 84.9% of ESCC patients (64 out of 86 cases). Furthermore, we also found that higher HAb18G/CD147 expression levels significantly correlated with lymph node metastasis, depth of tumor invasion and differentiation ( P < 0.05). But the expression levels of HAb18G/CD147 in lymph node metastatic tissues were almost equal to that in the primary tumor tissues. Furthermore, lymph node metastasis and expression of HAB18G/CD147 were independent prognostic indicators in ESCC. Conclusions The expression of HAb18G/CD147 might be involved in the progression and survival of ESCC. Therefore, HAb18G/CD147 could be a clinical marker for the poor prognosis in ESCC patients and may also be a potentially therapeutic target to improve the progression of ESCC.